Study on the static properties of spiral springs under static loading - Li, Zhixiang; Zhao, Zhen; Liu, Caishan; Wang, Qingyun (Applied mathematics and mechanics, 2021)
Spiral springs have a wide range of applications in various fields. As a result of the complexity of friction, few theoretical analyses of spring belts under static loading have been carried out. Considering the piecewise smooth property of the whole contact area, a simplified static model of spiral springs under loading is established in this paper. Besides, three main stress and friction distribution areas of the spring belt are proposed, namely, internal, transitional, and external regions. Since the outermost side of the spring is not subject to any pressure, a recursive method is adopted from the outside to the inside. The model provides the parameter conditions, i.e., the internal and external forces are independent or dependent. Therefore, the case that the whole contact region of the spring belt has one subregion, two subregions, and three subregions is obtained. The model gives a theoretical basis for the parameter optimization of spiral springs.